Endoscopic management of complications of chronic pancreatitis - Dumonceau, Jean-Marc (Baishideng Publishing Group Co., Limited, 2013)
Pseudocysts and biliary obstructions will affect approximately one third of patients with chronic pancreatitis (CP). For CP-related, uncomplicated, pancreatic pseudocysts (PPC), endoscopy is the first-choice therapeutic option. Recent advances have focused on endosonography-guided PPC transmural drainage, which tends to replace the conventional, duodenoscope-based coma immediately approach. Ancillary material is being tested to facilitate the endosonography-guided procedure. In this review, the most adequate techniques depending on PPC characteristics are presented along with supporting evidence. For CP-related biliary obstructions, endoscopy and surgery are valid therapeutic options. Patient co-morbidities (e.g., portal cavernoma) and expected patient compliance to repeat endoscopic procedures are important factors when selecting the most adapted option. Malignancy should be reasonably ruled out before embarking on the endoscopic treatment of presumed CP-related biliary strictures. In endoscopy, the gold standard technique consists of placing simultaneous, multiple, side-by-side, plastic stents for a one-year period. Fully covered self-expandable metal stents are challenging this method and have provided 50% mid-term success.